2019
DOI: 10.3389/fphys.2019.00122
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Characterization of Glycoside Hydrolase Family 16 Genes in Aedes aegypti Larvae: Identification of the Major Digestive β-1,3-Glucanase

Abstract: Insect β-1,3-glucanases belong to Glycoside Hydrolase Family 16 (GHF16) and are involved in digestion of detritus and plant hemicellulose. In this work, we investigated the role of GHF16 genes in Aedes aegypti larvae, due to their detritivore diet. Aedes aegypti genome has six genes belonging to GHF16 (Aae GH16.1 – Aae GH16.6), containing two to six exons. Sequence analysis suggests that five of these GHF16 sequences (Aae GH16.1, 2, 3, 5, and 6) contain the conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Various types of glucoside hydrolases are present in the genomes of phytophagous insects including beetles and moths 26 28 . While in the nematode Aphelenchoides besseyi and Aedes aegypti mosquito larvae, GH16 is suggested to be associated with glucan rich diets 29 , 30 . Previous studies on centipedes have also illustrated the presence of GH in venoms, where they are postulated to act as “spreading factors” that promote the pathological effects of other venom elements after envenomation, and also as antimicrobial factors 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Various types of glucoside hydrolases are present in the genomes of phytophagous insects including beetles and moths 26 28 . While in the nematode Aphelenchoides besseyi and Aedes aegypti mosquito larvae, GH16 is suggested to be associated with glucan rich diets 29 , 30 . Previous studies on centipedes have also illustrated the presence of GH in venoms, where they are postulated to act as “spreading factors” that promote the pathological effects of other venom elements after envenomation, and also as antimicrobial factors 31 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their immune role, these proteins seem to have a digestive implication when they are expressed in the insect's midgut [42]. Interestingly, we have shown in the comparative proteome of R. prolixus midgut [43,44] that T1HU92 (ML domain protein) expression level increases in response to blood feeding.…”
Section: Nonself Perception and Recognitionmentioning
confidence: 85%
“…Proteins containing ABHD, including kraken protein, have diverse catalytic functions such as proteases, esterases, nucleases, glycosidases, and phosphatases. Most studies focusing on the hydrolase functions of mosquitoes, involving glucanases (Souza et al, 2019), epoxide hydrolases (Xu et al, 2014), and acetylcholinesterases (Dou et al, 2013), have suggested that they were not related to the response to pathogen infection. However, the range of oocyst numbers was variable depending on the blood sample used, T A B L E 5 The total binding energy of 20 top-scoring compounds which bound to AdFUEBP homology model.…”
Section: Discussionmentioning
confidence: 99%